H-BET Historic Built Environment Typologies. Open spaces and SUOD events in the compact historic town - Edoardo Currà; Alessandro D'Amico; Martina Russo; Marco Angelosanti; Cassia De Lian Cui; Enrico Quagliarini (Vitruvio: International Journal of Architectural Technology and Sustainability)
The relationships between the Built Environment (BE) and SUdden-Onset Disasters (SUOD) are increasingly the focus of hazard mitigation investigation. Specifically, in the Historic Built Environment (HBE), defined as the network of buildings, infrastructure, and open spaces of the compact historic city, recent and past events have shown the need for an elevation of the resilience of the resident community. Previous studies by the author’s research team have objectified the characterisation of HBEs prone to SUODs. What emerged was the primary importance of open spaces in the Built Environment as elements to be characterised with respect to possible emergency phases and BE user behaviour. Specifically, the Historic Built Environment Typologies (H-BETs) can help to evaluate user behaviour during and after the event. Focusing on the role of the classification of the open spaces, the paper presents the H-BETs and their potential role in the multi-risk assessment of the compact historic town. The specific risk conditions of the urban areas (e.g., crowding, the complexity of the overall form of BEs, characteristics of built elements, uses of BEs), and the physical characteristics of historic urban BE (e.g., the height of the built fronts, number, and type of accesses, the slope of the ground) are considered together in order to propose a classification of different type of open spaces, starting from morphological classes towards the definition of a complete typological categorisation, representative of the urban system’s variables that interact with the identified SUOD hazards.